African Swine Fever Outbreak Investigation on Large Commercial Pig Farm in Serbia - Nešković Milijana (Sciendo, 2021)
The first confirmed case of African Swine Fever (ASF) in Serbia occurred in 2019. Since then, numerous outbreaks in domestic pigs and wild boars have been reported. Until April 2021, all the detected ASF cases were in backyard pigs. Beside backyard and smallholders farming systems as a dominant pig production system in Serbia, large commercial pig farms can also be found, located mostly in villages. In the beginning of April 2021, a large commercial farrow-to-finish pig farm in Serbia with almost 19,000 animals was affected with the ASF virus. The pig farm analysed in this paper is located in an area where ASF was confirmed earlier in both backyard and wild boars. In this study, we describe the overall epidemiological course of the ASF outbreak. Epidemiological investigation using a hypothesis-based approach was conducted in order to reconstruct the disease course until the official notification. All the available data from the farm were analysed with the aim to determine the high-risk period (HRP). Some of the key points to consider when it comes to the sources of infection and entry route of ASF are the following: contamination of the area in the immediate vicinity of the farm, risky human activities, irregularities and some omissions in the external farm biosecurity and immediate proximity of the city waste-yard where the communal waste is disposed of. It was concluded that when commercial pig farms are surrounded by villages with a large number of backyards, hence the anthropogenic factor is the key risk factor for ASF spreading.